Effectiveness of Public Transportation Route Licensing Services at the Riau Province Transportation Agency - Miftahul Jannah; Monalisa Monalisa (International Journal of Social Sciences, 2026)
The provision of public transport route licensing by the Riau Provincial Department of Transportation is essential to ensure the legality, safety, and orderliness of public transportation. However, persistent challenges in the field include the prevalence of illegal transport operations, delays in permit issuance, and low compliance among transport operators in securing official permits. This study aims to analyze the effectiveness of public transport route licensing services at the Riau Provincial Department of Transportation and to identify the inhibiting factors within the service process. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews with key informants, and document analysis. Service effectiveness was assessed using Steers' (1985) five indicators productivity, service quality, efficiency, flexibility, and user satisfaction. The findings indicate that licensing services have generally functioned quite well, supported by the integration of the Online Single Submission (OSS) system, although performance remains suboptimal. The main obstacles identified include a complex administrative and technical document verification process that causes delays, low interest among Intra-Provincial Urban Transport (AKDP) operators in applying for permits, regulations perceived as burdensome for small-scale travel businesses, and weak post-issue supervision in the field.